Developing Global Warming Module Based on Education for Sustainable Development to Increase Middle School Students Understanding and Sustainability Awareness - Putri, Senda Tiara; Fardhani*, Indra; Mulyati, Yayuk; Kurniawan, Bakhrul Rizky; Putri, Adella Anfidina (Jurnal Pendidikan Sains Indonesia, 2024)
The environmental crisis, which is a global problem, can be overcome by increasing sustainability awareness. The education for sustainable development (ESD) based global warming module can increase understanding and sustainability awareness. The goal of this research was to create a module based on ESD that deserves to be tested for its effectiveness in raising junior high school students understanding and sustainability awareness of global warming. The development procedure is based on the ADDIE model (analyze, design, develop, implement, and evaluate) data collection techniques using interviews, questionnaires, and pretest-posttest questions. The data analysis techniques used are the descriptive qualitative technique, percentage analysis, readability test, validity and reliability test, normality and homogeneity test, independent sample t-test, N-gain test, and effect size test. The results of media and material validation tests show very valid criteria. The results of the N-gain test in the post-test control class showed low criteria, while those in the experimental class showed medium bars. The outcomes of the effect size test in the post-test control and practical classes show high criteria. This research indicates that the modules developed are valid and effective for increasing students' understanding and sustainability awareness